Factors Associated With Osteoarthritis Of The Knee In Former Professional Male Footballers In Bangladesh (KYAMC Journal, 2020)
Background:: Osteoarthritis is one of the commonest disabilities that affect human life. Knee joint is most commonly affected by osteoarthritis. The professional footballers are exposed to heavy and prolonged physical activities that often exceed normal health capacities during both training and competition and are at risk of developing knee osteoarthritis of the knee (KOA).Objective: To evaluate the factors related to KOA in former professional male footballers in Bangladesh.Materials and Methods: This was a multicenter cross-sectional study. Purposively Selected footballers subsequently underwent knee radiographs at Bangabandhu Sheikh Mujib Medical University (BSMMU) and Kurmitola General Hospital (KGH). Patients were examined at Sports Medicine Clinic of KGH and Department of Physical Medicine and Rehabilitation of BSMMU from January 2019 to December 2019.Results: The mean age of ex footballers was 59.49±9.19 years. We found 46.55% prevalence of KOA among footballers. Among 174 footballers 37.63% had history of familial OA and 8.62% had gout. An average matches played by a footballer was 497 and average training in career was 3924 hours. We found knee injury, BMI, family history of OA, gout and total matches played were significant risk factors for KOA. Other did not proved significant.Conclusion: Knee injury was the prime factor here for causing KOA later. So we need to give more attention in preventing knee injuries beside other strategies to reduce risk of developing KOA, moreover early diagnosis of KOA, modification of activities of daily living and exercise is needed.KYAMC Journal Vol. 11, No.-3, October 2020, Page 141-144